Preparation of PSAS-coated PEDOT composite material and Cr (VI) photocatalytic reduction performance of PSAS-coated PEDOT composite material
By in-situ polymerization of PEDOT on the surface of crystalline organic hybrid silver antimony sulfide PSAS particles to form PSAS@PEDOT-x composite material, the problems of low efficiency and stability in the treatment of Cr(VI)-containing wastewater by traditional methods are solved, and a highly efficient and stable photocatalytic reduction of Cr(VI) is achieved.
Patent Information
- Application Number
- CN202410718383.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-12-05
AI Technical Summary
Existing technologies are difficult to effectively treat Cr(VI)-containing wastewater. Traditional methods are easily limited by sludge generation, incomplete sedimentation, or high operating costs. The efficiency of photocatalytic reaction depends on the activity of the photocatalyst. Crystalline organic hybrid metal sulfides are rarely used in the photocatalytic reduction of Cr(VI).
In-situ polymerization was used to deposit the polymer PEDOT on the surface of crystalline organic hybrid silver antimony sulfide PSAS particles to form a PSAS@PEDOT-x composite material, which was used as a photocatalyst to reduce Cr(VI) under visible light.
PSAS@PEDOT-45 achieves 100% Cr(VI) reduction within 25 minutes, demonstrating highly efficient photocatalytic activity and cycle stability, adapting to different aquatic environments and maintaining excellent photocatalytic performance.
Smart Images

Figure CN121060604A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to application of a PSAS@PEDOT-x composite formed by coupling of an organic hybrid silver antimony sulfide PSAS and a polymer PEDOT in photocatalytic reduction of Cr(VI), and belongs to the field of catalysis. BACKGROUND
[0002] Cr(VI) is a common toxic chemical substance with serious carcinogenicity and is considered as one of the most dangerous pollutants. Cr(VI) widely exists in various industrial wastewater, including industrial wastewater generated in electroplating, textile and pigment industries. Since Cr(VI) can exist in the form of stable oxygen-containing acid radical in water bodies and has strong migration ability, it seriously threatens the safety of water environment. In order to change this situation, it is imminent to use effective and sustainable methods to treat Cr(VI)-containing wastewater. Traditional methods for treating Cr(VI) include ion exchange, adsorption and chemical precipitation. These methods are limited by sludge production, incomplete precipitation or high operation cost, and it is difficult to effectively and sustainably treat Cr(VI)-containing wastewater. Photocatalytic reduction method is considered as an effective means for treating Cr(VI)-containing wastewater. In the photocatalytic reaction, the photocatalyst can absorb photons to generate photo-generated electrons and holes, which can further lead to the formation of various active oxygen-containing radicals. Photo-generated electrons and active oxygen-containing radicals can reduce highly toxic Cr(VI) into Cr(III), and the toxicity of Cr(III) is about 1000 times lower than that of Cr(VI), and Cr(III) can be removed from the solution in the form of Cr2O3 or Cr(OH)3 precipitate under alkaline conditions. However, the efficiency of photocatalytic reaction is highly dependent on the activity of photocatalyst. Therefore, it is of great significance to develop high-activity photocatalyst for the application of photocatalytic reduction of Cr(VI).
[0003] Inorganic metal sulfides as a typical semiconductor photocatalyst have been widely used for treating Cr(VI)-containing wastewater. However, the application of crystalline organic hybrid metal sulfides as photocatalysts for reducing Cr(VI) is still relatively rare. Crystalline organic hybrid metal sulfides are composed of diverse organic ligands and metal sulfide frameworks, and have not only rich structural types, but also open metal-sulfur framework structures. These characteristics of crystalline organic hybrid metal sulfides make them expected to be used as high-activity photocatalysts for reducing Cr(VI). In addition, the crystalline organic hybrid metal sulfides can be composited with other materials to form heterojunction, which can improve the separation efficiency of photo-generated carriers and further improve the photocatalytic reduction performance of the composite material for Cr(VI). SUMMARY
[0004] The technical problem solved by the present application is: in view of the serious problem of Cr(VI) pollution in water bodies, the present application provides a series of crystalline organic hybrid metal sulfide-based composite materials PSAS@PEDOT-x (x = 15, 45, 90), and applies them as photocatalysts for photocatalytic reduction of Cr(VI). Under the conditions of a photocatalyst concentration of 1.0 g L -1 , pH = 3, and a K2Cr2O7 concentration of 100 mg L -1 , the reduction rate of PSAS@PEDOT-45 to Cr(VI) reaches 100% within 25 minutes. The present application expands the application of organic hybrid metal sulfides in the field of photocatalytic reduction of Cr(VI).
[0005] To solve the above technical problems, the technical solution provided by the present application is: after the crystals of a crystalline organic hybrid silver antimony sulfide PSAS are fully ground, a polymer PEDOT is deposited on the surface of the particles by an in-situ polymerization method, to obtain a PSAS@PEDOT-x composite material. The PSAS@PEDOT-x composite is used as a photocatalyst for photocatalytic reduction of Cr(VI) under visible light irradiation.
[0006] Preferably, a crystalline organic hybrid silver antimony sulfide [pipH2] 0.5 [Ag2SbS3] is prepared by a one-step solvothermal method, and is named PSAS.
[0007] Preferably, AgNO3 (1.013 mmol, 0.172 g), Sb2S3 (0.503 mmol, 0.171 g), S (4.023 mmol, 0.129 g), and piperazine (26.069 mmol, 2.009 g) are added to a 25 mL reaction kettle, and then placed in an oven at 190°C for 6 days, and naturally cooled to room temperature. The product is washed with water and ethanol to obtain yellow flaky crystals of PSAS.
[0008] Preferably, the PSAS crystallizes in a monoclinic system, and the space group is P21 / n. The compound has a two-dimensional honeycomb-like anion double-layer structure, and the doubly protonated piperazine cation is filled in the interlayer of the anion layer to balance the charge.
[0009] Preferably, 3,4-ethylenedioxythiophene monomers are polymerized on the surface of PSAS by an in-situ polymerization method, to obtain a PSAS@PEDOT-x composite material.
[0010] Preferably, the amount of 3,4-ethylenedioxythiophene monomers is 15 μL, 45 μL, and 90 μL, respectively. Therefore, the PSAS@PEDOT-x is PSAS@PEDOT-15, PSAS@PEDOT-45, and PSAS@PEDOT-90, respectively.
[0011] Preferably, in the PSAS@PEDOT-x composite, PEDOT is loaded on the surface of PSAS particles.
[0012] Preferably, when PSAS@PEDOT-x is used as a photocatalyst, its concentration is 1.0g / L -1 .
[0013] Preferably, for the photocatalytic reduction of Cr(VI) test, Cr(VI) is provided by K2Cr2O7, and the concentration of K2Cr2O7 is 100mg / L -1 .
[0014] Preferably, for the photocatalytic reduction of Cr(VI) test, the pH value of the Cr(VI)-containing solution is 3.
[0015] Preferably, in the test of photocatalytic reduction of Cr(VI), PSAS@PEDOT-45 composite material exhibits the best photocatalytic reduction of Cr(VI) activity.
[0016] Preferably, for the photocatalytic reduction of Cr(VI) performance test of PSAS@PEDOT-45 composite material, not only its photocatalytic reduction of Cr(VI) activity under visible light irradiation is tested, but also its photocatalytic reduction of Cr(VI) performance under sunlight irradiation and in natural water body is tested, proving the feasibility of its application in photocatalytic reduction of Cr(VI).
[0017] Beneficial effects:
[0018] The application discloses application of a PSAS@PEDOT-x composite formed by coupling of a crystalline organic hybrid silver antimony sulfide PSAS and a polymer PEDOT in photocatalytic reduction of Cr(VI), and belongs to the technical field of photocatalysis and heavy metal ion-containing wastewater treatment. The application selects PSAS with a unique honeycomb double-layer structure, loads the polymer PEDOT on the surface of the PSAS through in-situ polymerization, and determines the optimal amount of EDOT monomers and the polymerization time, and prepares a PSAS@PEDOT-45 composite material. When the PSAS@PEDOT-45 composite material is applied as a photocatalyst in photocatalytic reduction of Cr(VI), under the condition that the pH value is 3 and the concentration of K2Cr2O7 is 100mg / L -1 , the reduction rate of Cr(VI) reaches 100% in 25 minutes.
[0019] The product exhibits very excellent photocatalytic performance when applied as a photocatalyst in photocatalytic reduction of Cr(VI).-1 exhibited high photocatalytic activity. In 5 cycles of testing, PSAS@PEDOT-45 all exhibited high photocatalytic reduction of Cr(VI) ability, and its structure did not change significantly, exhibiting excellent cycle stability. In addition, in the water environment of tap water, lake water and river water, and under the condition of sunlight irradiation, the PSAS@PEDOT-45 complex can maintain high photocatalytic reduction of Cr(VI) performance.
[0020] The product exhibits excellent photocatalytic reduction of Cr(VI) performance can be attributed to the following two points:
[0021] (1) PSAS compound has a unique two-dimensional honeycomb double-layer structure, and the diprotonated piperazine cation is filled between the layers, so that there is a large interlayer spacing between the anion layers, which provides enough space for the migration of Cr(VI) between the layers. In addition, the diprotonated piperazine cation can interact with the Cr(VI) oxygen-containing anion through electrostatic attraction, thereby promoting the adsorption of Cr(VI).
[0022] (2) Based on the band structure of PSAS and the HOMO and LUMO energy levels of PEDOT, a Z-type heterojunction is formed between PSAS and PEDOT, and the photo-generated electrons of PEDOT can recombine with the holes generated by PSAS. This hinders the recombination of photo-generated electrons and holes of PSAS, improves the utilization rate of photo-generated electrons, and is conducive to the photocatalytic reduction of Cr(VI). BRIEF DESCRIPTION OF DRAWINGS
[0023] The application will be further described below in conjunction with the drawings.
[0024] Figure 1 is a structural diagram of PSAS.
[0025] Figure 2 is a PXRD spectrum of PSAS crystal obtained in Example I.
[0026] Figure 3 is a PXRD spectrum of PSAS@PEDOT-x complex obtained in Example 2.
[0027] Figure 4 is a FTIR spectrum of PSAS@PEDOT-x complex obtained in Example 2.
[0028] Figure 5 a is a SEM image of PSAS obtained in Example 1, Figure 5 b-5d are SEM images of PSAS@PEDOT-15, PSAS@PEDOT-45 and PSAS@PEDOT-90 obtained in Example 2, respectively.
[0029] Figure 6 Photocatalytic reduction of Cr(VI) performance of different catalysts for Example 3 in K2Cr2O7 solution with pH = 3, concentration of 100 mg L -1
[0030] Figure 7 Photocatalytic reduction of Cr(VI) performance of PSAS@PEDOT-45 for Example 4 in K2Cr2O7 solution with concentrations of 50, 100, 150 and 200 mg L -1
[0031] Figure 8 Photocatalytic reduction of Cr(VI) performance of PSAS@PEDOT-45 for Example 5 in K2Cr2O7 solution with pH values of 2, 3, 4 and 6.
[0032] Figure 9 Photocatalytic reduction of Cr(VI) performance of PSAS@PEDOT-45 for Example 6 in deionized water, tap water, Nanjing Xuanwu Lake water and Nanjing Yangtze River water environments.
[0033] Figure 10 Photocatalytic reduction of Cr(VI) performance of PSAS@PEDOT-45 for Example 6 under sunlight irradiation.
[0034] Figure 11 Photocatalytic reduction of Cr(VI) performance of PSAS@PEDOT-45 for Example 7 in 5 cycles of tests.
[0035] Figure 12 PXRD patterns of PSAS@PEDOT-45 for Example 7 before and after 5 cycles of tests.
[0036] Figure 13 Structure of PSAS and photocatalytic reduction of Cr(VI) performance of different catalysts. DETAILED DESCRIPTION
[0037] The application is further explained and described below:
[0038] 1. The successful preparation of PSAS crystals with unique two-dimensional honeycomb-like double-layer structure is confirmed, see Example 1.
[0039] 2. The successful preparation of PSAS@PEDOT-x composite is confirmed, see Example 2.
[0040] 3. The photocatalytic reduction of Cr(VI) by PSAS@PEDOT-x under visible light irradiation provided by a xenon lamp was investigated, see Example 3.
[0041] 4. The effect of different Cr(VI) concentrations on the photocatalytic reduction of Cr(VI) by PSAS@PEDOT-45 was investigated, see Example 4.
[0042] 5. The effect of the pH of the Cr(VI) solution on the photocatalytic reduction of Cr(VI) by PSAS@PEDOT-45 was investigated, see Example 5.
[0043] 6. The photocatalytic reduction of Cr(VI) by PSAS@PEDOT-45 in different water bodies was investigated, see Example 6.
[0044] 7. The photocatalytic reduction of Cr(VI) by PSAS@PEDOT-45 under sunlight irradiation was investigated, see Example 6.
[0045] 8. The recycling stability of PSAS@PEDOT-45 as a photocatalyst in the photocatalytic reduction of Cr(VI) was investigated, see Example 7.
[0046] Example 1:
[0047] Synthesis of PSAS compound: AgN03(1.013 mmol, 0.172 g), Sb2S3(0.503 mmol, 0.171 g), S (4.023 mmol, 0.129 g) and piperazine (26.069 mmol, 2.009 g) were weighed and mixed uniformly, then added to a 25 mL polytetrafluoroethylene reaction kettle, which was then packaged in a stainless steel shell, and then placed in an oven at 190 °C for 6 days. The reaction kettle was naturally cooled to room temperature, and the product was washed with water and ethanol to obtain a large amount of yellow flaky crystals.
[0048] Figure 1 The structure of the obtained PSAS is shown in the figure, and the PSAS compound has a unique two-dimensional honeycomb double-layer structure, and the layered structure is stacked along the b-axis direction, and the double-protonated piperazine cation is filled between the layers.
[0049] Figure 2 The PXRD pattern of the obtained PSAS crystal is shown in the figure, and the diffraction peaks are consistent with the diffraction peaks simulated based on single crystal XRD data, which proves the successful preparation of the pure phase target product.
[0050] Example 2:
[0051] Preparation of PSAS@PEDOT-x: 100 mg of PSAS crystals synthesized in Example 1 was placed in a mortar and ground for 30 min to obtain a yellow powder of PSAS. 100 mg of PSAS powder and different amounts of EDOT (15 μL, 45 μL and 90 μL) were dispersed in 40 mL of HC1 solution (pH = 2.5) and stirred for 30 min. Then 20 mL of ammonium persulfate solution with different concentrations (1.5 mg L -1 , 4.5 mg L -1 and 9.0 mg L -1 ) was injected into the mixed solution of PSAS and EDOT at a rate of 0.6 mL min -1 using a syringe pump, followed by stirring at room temperature for 12 h. After centrifugation, washing and drying, dark green powders of PSAS@PEDOT-x (x = 15, 45, 90) were obtained.
[0052] Figure 3 PXRD patterns of PSAS@PEDOT-x (x = 15, 45, 90) composites are shown, which can be well matched with the simulated peaks of PSAS, indicating that the crystal structure of PSAS can be well maintained after grinding and in-situ polymerization of PEDOT.
[0053] Figure 4 FTIR spectra of PSAS, PEDOT and PSAS@PEDOT-x (x = 15, 45, 90) are shown. Compared with PSAS, PEDOT, PSAS@PEDOT-15, PSAS@PEDOT-45 and PSAS@PEDOT-90 all exhibit a characteristic absorption peak at 1517 cm -1 , which corresponds to the stretching vibration of thiophene ring, indicating that PEDOT is successfully loaded on the surface of PSAS particles.
[0054] Figure 5 SEM images of PSAS and PSAS@PEDOT-x (x = 15, 45, 90) are shown. The surface of ground PSAS is relatively smooth. After loading PEDOT, the surface of PSAS microcrystals begins to become rough, indicating the successful loading of PEDOT on the surface of PSAS microcrystals. With the increase of PEDOT loading, the surface of PSAS microcrystals becomes more rough, indicating that more PEDOT is loaded on the surface of PSAS microcrystals.
[0055] Example 3:
[0056] Photocatalytic reduction of Cr(VI) test: 50 mg of PSAS and PSAS@PEDOT-x prepared in Example 1 and Example 2 were used as photocatalyst and dispersed in 30 mL of HC1 solution (pH = 2) respectively, stirred for 30 min, and after centrifugation and drying, the protonated photocatalyst was obtained. Then 50 mg of photocatalyst was added to 50 mL of K2Cr207 solution with a concentration of 100 mg L -1 , pH = 3, ultrasonic dispersion, magnetic stirring in the dark for 120 min to reach adsorption-desorption equilibrium. Then the photocatalytic reduction of Cr(VI) experiment was carried out under visible light irradiation, using a 300 W xenon lamp with a 420 nm filter as the light source, and the temperature of the reaction system was controlled at 25°C by using a condensing device.
[0057] During the photocatalytic reaction, 2 mL of K2Cr207 solution was taken out every 5 min. After centrifugation, 1 mL of supernatant was taken, and the concentration of Cr(VI) was measured by diphenyl urea (DPC) method on a UV-visible spectrophotometer. The removal rate of Cr(VI) at different reaction times was calculated by the formula η = C t / C0 x 100%, where C t is the instantaneous concentration of the solution, and C0 is the initial concentration of the solution. After calculation, the photocatalytic reduction of Cr(VI) performance of PSAS and PSAS@PEDOT-x was obtained. As shown in Figure 6 , PSAS@PEDOT-45 can completely reduce Cr(VI) with a concentration of 100 mg L -1 in 25 min, and PSAS@PEDOT-15 and PSAS@PEDOT-90 can also completely remove Cr(VI) in 40 min, and the photocatalytic activity is obviously better than that of PSAS. It is proved that PSAS@PEDOT-x as a photocatalyst has excellent photocatalytic activity.
[0058] Example 4:
[0059] Photocatalytic activity test of PSAS@PEDOT-45 under different Cr(VI) concentrations: 50 mL of K2Cr207 solution with different concentrations (50, 100, 150 and 200 mg L -1 ) was prepared, and the pH was adjusted to 3. Then 50 mg of protonated PSAS@PEDOT-45 was added to the above solution respectively, ultrasonic dispersion, magnetic stirring in the dark for 120 min to reach adsorption-desorption equilibrium. Then the photocatalytic reduction of Cr(VI) experiment was carried out under visible light irradiation, and the temperature of the reaction system was controlled at 25°C by using a condensing device. The removal rate of Cr(VI) at different reaction times was calculated by the method in Example 3. As shown in Figure 7 , for the concentration of 50 mg L-1 Cr(VI) solution, PSAS@PEDOT-45 was able to completely reduce it within 5 minutes; even at a high concentration of 200 mg L -1 PSAS@PEDOT-45 was still able to reduce 81.1% of Cr(VI) within 40 minutes.
[0060] Example 5:
[0061] Photocatalytic activity test of PSAS@PEDOT-45 in Cr(VI) solutions with different acidity: 4 portions of 50 mL K2Cr2O7 solution with a concentration of 100 mg L -1 were prepared, and their pH values were adjusted to 2, 3, 4 and 6, respectively. Then 50 mg of protonated PSAS@PEDOT-45 was added to the above solutions, which were ultrasonically dispersed and magnetically stirred in the dark for 120 minutes to achieve adsorption-desorption equilibrium. Then the photocatalytic reduction of Cr(VI) was carried out under visible light irradiation, and the temperature of the reaction system was controlled at 25°C. The removal rate of Cr(VI) at different reaction times was calculated by the method in Example 3. Figure 8 The photocatalytic activity of PSAS@PEDOT-45 in different acidic environments was demonstrated. When the pH values were 2, 3, 4 and 6, the reduction rates of Cr(VI) by PSAS@PEDOT-45 within 10 minutes were 100%, 94.3%, 75% and 47.7%, respectively.
[0062] Example 6:
[0063] Photocatalytic reduction of Cr(VI) performance test of PSAS@PEDOT-45 in different water bodies: 4 portions of 50 mL K2Cr2O7 solution with a concentration of 100 mg L -1 were prepared, and their pH values were adjusted to 2, 3, 4 and 6, respectively. Then 50 mg of protonated PSAS@PEDOT-45 was added to the above solutions, which were ultrasonically dispersed and magnetically stirred in the dark for 120 minutes to achieve adsorption-desorption equilibrium. Then the photocatalytic reduction of Cr(VI) was carried out under visible light irradiation, and the temperature of the reaction system was controlled at 25°C. The removal rate of Cr(VI) at different reaction times was calculated by the method in Example 3. As Figure 9As shown, compared with deionized water, the adsorption rate of PSAS@PEDOT-45 to Cr(VI) in tap water, lake water and river water is all weakened, but PSAS@PEDOT-45 can still exhibit high photocatalytic activity in the photocatalytic process, and can still completely reduce Cr(VI) in the three water bodies within 35 minutes. This shows that PSAS@PEDOT-45 has good adaptability to different water body environments, and further shows that PSAS@PEDOT-45 has application value for treating actual industrial wastewater.
[0064] Performance test of PSAS@PEDOT-45 in photocatalytic reduction of Cr(VI) under sunlight irradiation: 50 mg of protonated PSAS@PEDOT-45 was added to 50 mL of K2Cr2O7 solution with a concentration of 100 mg L -1 , pH = 3, ultrasonic dispersion, magnetic stirring in the dark for 120 minutes to reach adsorption-desorption equilibrium. Then the photocatalytic reduction of Cr(VI) experiment was carried out under sunlight irradiation. The method in Example 3 was used to calculate the removal rate of Cr(VI) at different reaction times. Figure 10 The photocatalytic reduction of Cr(VI) performance of PSAS@PEDOT-45 under sunlight irradiation from 9:00 am to 16:00 pm was demonstrated. Although the photocatalytic reduction of Cr(VI) performance of PSAS@PEDOT-45 under sunlight irradiation in different time periods was lower than that under xenon lamp irradiation, it still maintained high photocatalytic activity. This shows that PSAS@PEDOT-45 as a photocatalyst for photocatalytic reduction of Cr(VI) has potential practical application value.
[0065] Example 7:
[0066] Cyclic stability test of PSAS@PEDOT-45 in photocatalytic reduction of Cr(VI): 50 mg of protonated PSAS@PEDOT-45 was added to 50 mL of K2Cr2O7 solution with a concentration of 100 mg L -1 , pH = 3, ultrasonic dispersion, magnetic stirring in the dark for 120 minutes to reach adsorption-desorption equilibrium. Then the photocatalytic reduction of Cr(VI) experiment was carried out under visible light irradiation, and the temperature of the reaction system was controlled at 25°C. The method in Example 3 was used to calculate the removal rate of Cr(VI) at different reaction times. The PSAS@PEDOT-45 after reaction was immersed in HNO3 solution with pH = 1.5, then washed with deionized water and ethanol for 3 times and dried. The dried product was used to repeat the above process, and so on, a total of 5 cycles of test were carried out. Figure 11The performance of PSAS@PEDOT-45 in photocatalytic reduction of Cr(VI) in 5 cycles is shown in the figure. In the 5th cycle, the reduction rate of PSAS@PEDOT-45 to Cr(VI) can still reach 98.6% in 30 minutes. As shown in Figure 12 PXRD characterization proves that PSAS@PEDOT-45 still maintains its structural stability after 5 cycles, indicating that PSAS@PEDOT-45 has excellent cycle stability as a photocatalyst for photocatalytic reduction of Cr(VI).
Claims
1. An organic hybrid silver antimony sulfide [pipH2] 0.5 The use of PSAS@PEDOT-x (x = 15, 45, 90) composites formed by coupling of [Ag2SbS3] (PSAS) with poly(3,4-ethylenedioxythiophene) (PEDOT) in photocatalytic reduction of Cr(VI). Characterized in that: The compound PSAS has a honeycomb-like two-dimensional anionic bilayer [Ag2SbS3] n n- The two-dimensional anionic layer is stacked in the form of A-B-A-B. The diprotonated piperazine cation is filled between the layers of the [Ag2SbS3] n n- layer. These piperazine cations can adsorb Cr(VI) oxyanions through electrostatic interaction, thereby accelerating the photocatalytic reduction of Cr(VI). In addition, the surface-loaded PEDOT of PSAS can enhance the separation efficiency of photo-generated carriers of the PSAS@PEDOT-x composite, thereby improving the photocatalytic reduction of Cr(VI) performance of the PSAS@PEDOT-x composite.
2. The method of claim 1, wherein the PSAS@PEDOT-x composite is prepared by: PSAS@PEDOT-x composites were prepared by solvothermal method and in-situ polymerization. Specifically, 25 mL of reaction vessel was added with AgNO3(1.013 mmol, 0.172 g), Sb2S3(0.503 mmol, 0.171 g), S(4.023 mmol, 0.129 g) and piperazine (26.069 mmol, 2.009 g), and then placed in an oven at 190 °C for 6 days. After natural cooling to room temperature, the product was washed with water and ethanol to obtain yellow flake-like crystals of PSAS. The crystals of PSAS were then ground to obtain yellow powder. 100 mg of PSAS powder and different amounts of EDOT (15 μL, 45 μL and 90 μL) were dispersed in 40 mL of HCl solution (pH = 2.5) and stirred for 30 min. Then 20 mL of ammonium persulfate solution with different concentrations (1.5 mg L -1 , 4.5 mg L -1 and 9.0 mg L -1 ) was injected into the mixture of PSAS and EDOT at a rate of 0.6 mL min -1 using a syringe pump, followed by stirring at room temperature for 12 h. After centrifugation, washing and drying, dark green powders of PSAS@PEDOT-x (x = 15, 45, 90) were obtained.
3. The photocatalytic reduction of Cr(VI) by PSAS@PEDOT-x composite material as claimed in claim 1, characterized in that: Before the photocatalytic experiment, the PSAS@PEDOT-x catalyst was protonated by stirring in 30 mL of HCl solution (pH = 2) for 30 min.
4. The PSAS@PEDOT-x composite material for photocatalytic reduction of Cr(VI) as claimed in claim 1, wherein: The photocatalytic reduction of Cr(VI) was carried out at pH = 3.
5. The photocatalytic reduction of Cr(VI) by PSAS@PEDOT-x composite material as claimed in claim 1, characterized in that: In the photocatalytic experiment, the amount of PSAS@PEDOT-x catalyst was 1.0 g L -1 .
6. The photocatalytic reduction of Cr(VI) by PSAS@PEDOT-x composite material as claimed in claim 1, characterized in that: Under visible light irradiation, catalytic reduction of K2Cr207solution, the concentration of K2Cr207is 100 mg L -1 .